Processo de execução e a sua relativização pela incidência das excludentes de responsabilidade e o princípio da dignidade da pessoa humana - Caram Junior, Moacyr (2007)
The elaboration of this doctoral dissertation was motivated mainly by the bleakness of all sorts, which assault the country. The fragility of the institutions, the unemployment, and the political and economical uncertainty are some examples which lead to great turbulences and, consequently, to the most diverse fears in the society. Considering such circumstances and, with no harm of the impetuous quest for the effectiveness of the jurisdictional services, it has been defended, in observance of the isonomy principle, the necessity to be attentive with the dignity of the person of the debtor. Even though in the ambit of the executory process, there must be properly surveyed by the magistrates if the breach of contract occurs simply by unjustifiable willingness, that is, if the obligation was not fulfilled simply for not wanting to, or if the obligatory dishonor elapsed due to unmanageable circumstances which escape the human capacity. This is the major quest. It has been asserted that the constitutional principles must direct the positioning of the Judiciary, thus being, sublimate the principle of dignity of the person is an imposed measure, in harmony with the contemporaneous anthropocentric theories. Thus, the ordinary legislator is the most responsible for the protection of the Brazilian society in the last years, heartened by the instabilities, which ravage Brazil. Due to these instabilities, the denominated exculpatory of responsibility, as the unforeseeable circumstances or force majeure, in addition to the institution of the excessive onerous, must be minutely and scientifically measured by the Judiciary, when they are to be the object of the discussion. It has been defended to be impossible the exactness and certitude in an environment of uncertainties, as the one we ve been living in. It has been verified to be perfectly possible, in the executory transactions, such institutions to be focused, when the bleach of contract is connected to superior and irresistible circumstances, and, being consistent the evidences, the force procedure must not prosper, standing out, fundamentally, the principle of dignity in aid of the debtor. It has also been observed that, beyond the proper instrument of defense foreseen, impugnation when the fulfillment of the sentence, and embargo of the debtor, when the execution has as objective extra judicial title, it is available for the obligated other various procedural instruments to defend himself and highlight the incidence of the excludents. At last, the present research conclude that, without the burdensome of the necessary effectiveness which must be tailored the jurisdictional services, it is only the sensibility of the magistrate that can measure and balance properly the relation between the bleach of contract, the obligational excludents and the dignity of the person of the debtor. The judiciary duty relate not necessarily in the fulfillment of the obligatio, but so with the clear intention of the debtor in wanting to satisfy what he indebted